The Effect of Lavender Aromatherapy on Reducing Anxiety in the Context of Nursing Care: A Literature Review - Sembiring, Nur Maghribi; Sembiring, Atikah Marhamah; Sembiring, Muhammad Simba (Journal of Bionursing, 2026)
Background : Anxiety is a feeling of fear about something that occurs, caused by the anticipation of danger, and serves as a signal that helps individuals prepare to take action in the face of a threat. Lavender is often used in aromatherapy because it can provide relaxation and has a sedative effect that is very helpful for people experiencing excessive anxiety. Relaxation techniques are a way to reduce anxiety. One relaxation technique that can be used is aromatherapy. Aim This study aims to determine the effect of lavender aromatherapy on reducing anxiety levels. Method : The data used in this study are secondary data obtained from previous research. The data sources were articles or journals relevant to this topic. Articles were obtained from 2021-2025. Data searches were conducted using Google Scholar with the keywords "lavender aromatherapy for anxiety," Proquest with the keywords "lavender aromatherapy and anxiety," and ScienceDirect with the keywords "lavender aromatherapy or anxiety." The search resulted in 1,327 articles. 13 articles were relevant to the literature review. Result : Several findings obtained by the authors regarding non-pharmacological therapy using lavender can be used to manage anxiety levels in clients such as: pregnant women in their third trimester, pre-operative patients, women about to give birth, hemodialysis patients, patients before tooth extraction, and is beneficial for improving sleep quality. Conclusion : The use of lavender